2010
DOI: 10.1073/pnas.0913054107
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Evidence for a functional role of IgE anticitrullinated protein antibodies in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a systemic autoimmune disease involving inflammation of the joints. Among the autoantibodies described in RA, anticitrullinated protein antibodies (ACPAs) are highly specific and predictive for RA. In addition, ACPAs have been implicated in the pathogenesis of RA. However, a direct functional response of immune cells from ACPA + RA patients toward citrullinated proteins has not been demonstrated. In this study, we show that exposure to citrullinated antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 34 publications
3
54
0
Order By: Relevance
“…Oral treatment with another PI3Kd inhibitor, IC87114 (Sadhu et al, 2003), demonstrated a similar effect, implicating the d isoform activity rather than g in our studies (Zhang et al, 2008). Although the role of IgE in RA is not well defined, the presence of IgE anticitrullinated protein antibodies in RA patients supports a possible relationship of IgE and RA (Schuerwegh et al, 2010). Interestingly, phase I studies in humans have not shown an increase in IgE levels and suggest that this might be a rodent-specific phenomenon (Infinity Pharmaceuticals, unpublished observations).…”
Section: Discussionsupporting
confidence: 55%
“…Oral treatment with another PI3Kd inhibitor, IC87114 (Sadhu et al, 2003), demonstrated a similar effect, implicating the d isoform activity rather than g in our studies (Zhang et al, 2008). Although the role of IgE in RA is not well defined, the presence of IgE anticitrullinated protein antibodies in RA patients supports a possible relationship of IgE and RA (Schuerwegh et al, 2010). Interestingly, phase I studies in humans have not shown an increase in IgE levels and suggest that this might be a rodent-specific phenomenon (Infinity Pharmaceuticals, unpublished observations).…”
Section: Discussionsupporting
confidence: 55%
“…This finding has made considerable impact, as it has opened up the way to relevant and novel insights into RA-diagnosis and etiopathology (1). For example, ACPA are now part of the new American College of Rheumatology/ European League Against Rheumatism criteria for RA (18), and have been implicated in RA-pathogenesis, both in animal models (19)(20)(21) and in ex vivo human studies (22)(23)(24)(25). Importantly, the description of ACPA has led to the realization that RA constitutes at least two clinical syndromes that share many clinical features, but differ with respect to genetic background, predisposing environmental factors and clinical progression/remission (3,4,(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…ACPA have all immunoglobulin isotypes including IgM [40] and IgE ACPA [41]. IgM-CCP is present in early samples from both patients with UA and patients with RA, as well as in long-term follow-up samples from patients with RA [40].…”
Section: Acpa Isotypesmentioning
confidence: 97%